2019
DOI: 10.1038/s41598-019-53068-7
|View full text |Cite
|
Sign up to set email alerts
|

3D Deformation Patterns of S Shaped Elastic Rods as a Pathogenesis Model for Spinal Deformity in Adolescent Idiopathic Scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) is a three-dimensional (3D) deformity of the spinal column in pediatric population. The primary cause of scoliosis remains unknown. The lack of such understanding has hampered development of effective preventive methods for management of this disease. A long-held assumption in pathogenesis of AIS is that the upright spine in human plays an important role in induction of scoliosis. Here, the variations in the sagittal curve of the scoliotic and non-scoliotic pediatric spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…It was previously showed that two axial subgroups exist in right thoracic AIS: loops shaped and lemniscate shaped [3,19]. The sagittal curvature of the spine relates to the pattern of the 3D deformity development, particularly the aforementioned axial subgroups of right thoracic AIS [19].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…It was previously showed that two axial subgroups exist in right thoracic AIS: loops shaped and lemniscate shaped [3,19]. The sagittal curvature of the spine relates to the pattern of the 3D deformity development, particularly the aforementioned axial subgroups of right thoracic AIS [19].…”
Section: Discussionmentioning
confidence: 96%
“…As shown previously, the axial projection of the curve carries important information for surgical and non-surgical management of the right thoracic AIS [6,[8][9][10]. It was also shown that the sagittal profile strongly relate to the patterns of axial deformation using mechanics of deformation in an elastic rod [3,11,12]. Here, it is studied if the axial projection of the curve varies within the Lenke types and whether that variation relates to the sagittal curvature of the spines within these subtypes.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations